An assessment of four decades of wave power variability - a critical requirement for coastal resilience - Hall, Candice (Department of Oceanography, 2023)
Wave power estimates and trend assessments are crucial for coastal management and resilience, as increases in wave power introduces significant risks of flooding and shoreline erosion. This study evaluates wave power trends at 29 National Oceanic and Atmospheric Administration (NOAA) National Data Buoy Center (NDBC) moored buoy sites with associated U.S. Army Corps of Engineers (USACE) Wave Information Study model estimates within the North Pacific Ocean, Hawaiian Islands, Gulf of Mexico and North Atlantic Ocean. This work is the first conclusive study to show spatially and temporally comparative observational and model wave power results, providing new information on the accuracy of model estimates using wave power as a proxy. Wave power data were interpolated to augment missing values and detrended for seasonality to facilitate testing of interannual and interdecadal trends in wave power. Results show that the majority of the eastern Pacific Ocean and Hawaii wave power trends are downward, with mixed slope wave power trends apparent within the Atlantic Ocean and Gulf of Mexico. Observational and model results show that wave power peaks in long term interannual trends are similar with respect to timing, but not magnitude. Variability in the wave power trend direction within each region suggests that site specific wave power trends should not be generalised to represent a large region, with regionally grouped annual maximum 90th percentiles obscuring the variability of individual site results. Prior to the calculation of these wave power estimates, a thorough interrogation of the quality of the observational wave data was conducted. Three tasks achieved confidence in these observational datasets: a) an evaluation of the effects of changing NDBC instrumentation technologies on data quality; b) the development of an independent, self describing, archive that mitigates for historical data storage issues; and c) the subsequent removal of identified discontinuities within the time series datasets. Instrumented buoy intercomparisons within the Pacific Ocean and U.S. Great Lakes prove that the recently deployed NDBC 2.1-m hulls show an increased wave data accuracy when compared to the legacy NDBC 3-m hulls for significant wave height, average wave period, and spectral signal-to-noise ratio, which allows for an increase in swell energy retention in the lower frequency spectral range. With confidence in the newly deployed NDBC platforms, this work then addressed NDBC data accessibility issues, as data are stored in multiple archives with unique storage, metadata, and quality control protocols. Known storage and quality control inconsistencies were removed and the validated data for all NDBC moored buoy stations are stored within a USACE Quality Controlled, Consistent (QCC) Measurement Archive, which is now a public database of best available historical NDBC data with verified metadata. Spectral wave data from this USACE QCC Archive were interpolated for frequency equivalency and used to recalculate the required wave power input parameters to ensure consistency through the historical datasets, successfully removing a number of previously identified time series discontinuations. With these data discontinuity corrections, uncertainties and inaccuracies are removed from the estimated wave power trends. Overall, this study highlights the undeniable need for accurate and consistent observational data that are essential for a realistic estimation of local wave climate studies, a vital requirement for all coastal risk management considerations. Although these observational and model wave power trends are U.S. specific, the methodologies developed within this work are applicable to datasets in any region.